1998
DOI: 10.1021/ja982786v
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Control of Intramolecular Electron Transfer in Calix[4]diquinones and Their Cationic Complexes

Abstract: The synthesis is described of a photoactive molecular dyad comprising a luminescent ruthenium(II) tris(2,2‘-bipyridyl) fragment covalently attached, via a methylene bridge, to a calix[4]arene receptor in which two of the four walls are benzoquinone functions. A distribution of interconverting conformers is expected for the calix[4]arene platform, including cone, partial cone, and 1,3-alternated forms, according to molecular dynamics simulations and NMR studies. Luminescence from the metal complex is quenched b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
0
12

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 159 publications
0
40
0
12
Order By: Relevance
“…[11] A [Ru-A C H T U N G T R E N N U N G (bpy) 3 ] 2 + fragment covalently attached to a calix [4]arene receptor varied its luminescence in response to cations such as barium(II). [12] Chemical oxygen sensors based on luminescence quenching of osmium complexes with 2,2,2-terpyridine [13] and a-diimine ligands [14] have also been reported. Owing to their electrochemical reversibility and stability in both their oxidised and reduced states, osmium complexes have also been employed as redox mediators in biocatalytic processes.…”
Section: Introductionmentioning
confidence: 99%
“…[11] A [Ru-A C H T U N G T R E N N U N G (bpy) 3 ] 2 + fragment covalently attached to a calix [4]arene receptor varied its luminescence in response to cations such as barium(II). [12] Chemical oxygen sensors based on luminescence quenching of osmium complexes with 2,2,2-terpyridine [13] and a-diimine ligands [14] have also been reported. Owing to their electrochemical reversibility and stability in both their oxidised and reduced states, osmium complexes have also been employed as redox mediators in biocatalytic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Some porphyrin derivatives linked covalently to ruthenium polypyridyl complexes have also been reported. [10][11][12][13][14][15][16][17][18] Recently, a number of covalently linked donor-acceptor systems have been extensively studied, but sometimes require time-consuming laborious synthetic works. Fortunately, a variety of donor-acceptor systems can be also assembled easily through noncovalent interactions such as ion-pairing, 19 H-bonding in DNA base-pairing, 20 or ligand binding on transition metal.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In the nineties, chromogenic recognition by chromophore-derived calix [4]arenes [2] and electrochemical recognition by quinone-derived calix [4]arenes [3] of alkali metal cations were reported. However, as far as we know, there are no reports on through-space interactions between two chromophores incorporated in a calixarene skeleton, although a paper dealing with intramolecular electron transfer in calix [4]arenediquinone derivatives appeared quite recently, [4] and multifunctional ion-sensing calixarenes that combine chromogenic and redox-active properties in one molecule are unknown. The combination of these properties could offer a promising route towards novel sensing materials.…”
mentioning
confidence: 99%
“…We have now designed and synthesized the novel calix [4]arenecrowns 1 and 2, together with their reference compounds 3 and 4, since the thienylene analogue of p-terphenoquinone as chromophore shows a strong absorption maximum in the visible region and affords a very stable radical anion and radical cation in electrochemical reactions. [5] We found that the two diametrically arranged chromophores of 1 and 2 undergo through-space exciton coupling on absorption of visible light.…”
mentioning
confidence: 99%
See 1 more Smart Citation